The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10943-012-9629-2
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Experiences of War Veterans Who Suffer from Combat-Related Post-Traumatic Stress Disorder: A Qualitative Study

Abstract: Recognition of the spiritual experiences of patients with post-traumatic stress disorder may be helpful in their rehabilitation. Accordingly, the present study has been carried out to determine the spiritual experiences of Iranian Muslim warriors who suffer from the previously mentioned disorder. In this qualitative study, 22 patients were selected using an objective-based sampling method and underwent an individual, semi-structured thorough interview. The data were analyzed using content analysis. The spiritu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Given the religious context of the Iranian society, this could be expected. A previous study suggested that in Islam, religion and spirituality are not separate concepts ( Nir et al, 2013 ). Shehan (2005) also argued that there can be an overlap between spirituality and religion.…”
Section: Discussionmentioning
confidence: 99%
“…Given the religious context of the Iranian society, this could be expected. A previous study suggested that in Islam, religion and spirituality are not separate concepts ( Nir et al, 2013 ). Shehan (2005) also argued that there can be an overlap between spirituality and religion.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study on veterans' wives stress disorder after the accident t in Iran showed the negative impact on family structure and function are particularly spouses of veterans. Negative emotions, lack of social support and negative view are the problems of this study (Sirati Nir, 2013). In a similar study in Afghanistan, it was also shown social support and quality of life of veterans' wives than husbands were non-veterans (Nicole 2013).…”
Section: Discussionmentioning
confidence: 58%
“…There is also a growing interest and scholarly persuasion for the medical field to include spiritual insights into its approach to healing and (again) to recognise the emotional needs of the patients. A wealth of evidence from empirical research published in medical journals shows that ‘spirituality’ has a positive effect on patients, carers and even medical practitioners, particularly when it comes to integrating spirituality in mainstream/allopathic approaches (Dunn and Horgas 2004; Sirati Nir et al 2013; Strawbridge et al 1997; Wachholtz et al 2007). This is often seen as repairing the more mechanical relationship between medical professional and patient, as well as recognising the importance of having a more empathetic and compassionate approach that can yield real results in recovery and the maintenance of health (Offenbaecher et al 2013).…”
Section: Spirituality and The Health Practitionermentioning
confidence: 99%